Recent Advances in Acidophile Microbiology: Fundamentals and Applications - Axel Schippers (Frontiers Research Topics, 2017)
There is considerable interest in pure and applied studies of extremophilic microorganisms, including those (acidophiles) that are active in low pH environments. As elsewhere in microbiology, this is a fast-developing field, and the proposed special issue of Frontiers highlights many of the more recent advances that have been made in this area. Authors from leading scientific groups located in North and South America, Australasia and Europe have contributed to this e-book, and the topics covered include advances in molecular, biochemical, biogeochemical and industrial aspects of acidophile microbiology.